Strategy of Servitization as a Tool for Achievement of Sustainable Development - Vlčková, Vladimíra; Vlček, David; Kanovska, Lucie (Univerzita Hradec Králové, 2021)
The reasons leading companies to the servitization strategy have recently been supplemented with society-wide global trend of striving for sustainable development. To be successful on the current markets, companies invest into services to increase the added value for the customer, diversification, and new income; to ensure the lock-in effect; to use the opportunity to grow and environmental burden reduction. These targets can be achieved by implementation of a strategic approach to servitization. In this paper, a research hypothesis that the manufacturers' strategic approach to servitization has a significant potential to affect achievement of sustainable development in a positive way has been constructed and discussed. The paper outcomes were drawn up based on the analysis, comparison, and synthesis of the information obtained (i) from a targeted professional literature review (ii) from an outcomes of the conducted electronic questionnaire survey. The questionnaire identified the level of the currently provided services related to their products and their expectations concerning an increased interest in services by their management, their customers, and their competitors. The outcomes should then help to direct companies in the Czech Republic to more extensive application of the servitization business model as a strategy supporting sustainable development.
Strategie servitizace jako nástroj k dosažení udržitelného rozvoje.
Keywords: servitization; services; manufacturing companies; sustainable development; servitizace; služby; výrobní společnosti; udržitelný rozvoj